Implementasi Mos dan E-Model Untuk Mengetahui Kualitas Komunikasi Jaringan VoIP - Prayogi, Satria Yudha; Sinaga, Sony Bahagia (LPPM UNIKA Santo Thomas Medan, 2021)
Voice Over Internet Protocol (VoIP) is a voice communication technology (voice) that uses IP which can be done electronically and in realtime. In building VoIP devices used such as IPPBX Server, IPPBX Gateway IP and other supporting devices such as mikrotik. To design VoIP generally implemented using a local area network (LAN) or a wireless local area network (WLAN). In this study, an analysis of the quality of VoIP network communication is to determine the problems caused by communication using VoIP, so that VoIP can be used to maximize the existing internet network. This VoIP network can save costs when communicating such as video communications or video conferencing.